POLA KONSUMSI PANGAN DAN STATUS GIZI ANAK BALITA DI DAERAH PANTAI KECAMATAN TELUK BETUNG TIMUR - Edelyn Adi Surya; Yaktiworo Indriani; Rabiatul Adawiyah (Lampung University, 2022)
This study aims to determine the pattern of food consumption and nutritional status of under five year children (toddlers) at the coastal areas of Teluk Betung Timur Distric with secondary data description method. This research is part of an umbrella study conducted in three areas in Bandar Lampung City, namely the highlands, lowlands, and coastal areas. The research sample in this study was 32 children aged 12-59 months. The data was analyzed by scoring the Desireble Dietary Pattern (DDP) to determine the food consumption pattern of toddlers and nutritional status assessment. The results showed the level of Energy Adequacy (TKE) of toddlers at the coastal areas of Teluk Betung Timur District of 110.13 percent which can be categorized as normal. Toddlers with an energy deficit of 5 toddlers (15.63%) while toddlers who experienced excess energy as much as 12 toddlers (37.15%). Only one toddler has a deficit of vitamin A while there are 19 toddlers who have a calcium deficit. The results showed the DDP of toddlers was only 72.32 which can be interpreted that DDP of toddlers have not reached the maximum score. Toddlers at the coastal areas of Teluk Betung Timur District who experienced malnutrition as much as 21.88 percent; stunting toddlers as much as 28.13 percent; and skinny toddlers as much as 15.63 percent.Key words: DDP, food consumption patterns, nutritional status, toddler